Launch of the London Centre for Nanotechnology. (December 2006) - Aeppli, Gabriel; Pankhurst, Quentin
Is nanomedicine an area with the promise that its proponents claim? Professors Gabriel Aeppli and Quentin Pankhurst explore the issues in light of the new London Centre for Nanotechnology (LCN) –– a joint enterprise between Imperial College and University College London –– opened on November 7, 2006. The center is a multidisciplinary research initiative that aims to bridge the physical, engineering and biomedical sciences. In this interview, Professor Gabriel Aeppli, LCN co-Director, and Deputy Director Professor Quentin Pankhurst discuss the advent and future role of the LCN with Nanomedicine ''s Morag Robertson. Professor Aeppli was formerly with NEC, Bell Laboratories and MIT and has more than 15 years'' experience in the computer and telecommunications industry. Professor Pankhurst is a physicist with more than 20 years'' experience of working with magnetic materials and nanoparticles, who now works closely with clinicians and medics on innovative healthcare applications. He also recently formed the new start-up company Endomagnetics Inc.